THE VOCABULARY MEMORISATION STRATEGY BEFORE ENTERING THE CLASSROOM AND THE USAGE OF THE MEMORISATION CARD - Hamzar Acha; Kurnia Kurnia (Eternal (English, Teaching, Learning & Research Journal), 2021)
This research aimed to explore the students’ responses towards the vocabulary memorisation strategy before entering the classroom and the usage of the memorisation card, and students’ vocabulary increase after joining the English class. This study employed a qualitative method which involved nine informants as the total samples. The results pinpointed precisely that the students gave profoundly positive attitudes to the application of vocabulary memorisation strategy before entering the classroom and the usage  of the memorisation card. Both strategies likewise boosted the students’ lexical items significantly which could be ultimately depicted by visible result proofs such as helping the students to accomplish their assignments at home or quizzes in the classroom without any assistance from Google, other devices or friends,  to aid them to produce more stocks of words in speaking practice and writing activity, to grasp the listening and reading comprehension, to pronounce the words correctly as well as to comprehend the meaning of the words or sentences. The result implication is that the educators both formal and informal institutions are recommended implicitly to apply those  practical strategies in order to address  students’ low motivation to study English and to escalate their four language skills and subskills rapidly.